Expression of Cytokines in Porcine Iris, Retina and Choroidal Tissues Stimulated by Microbe-associated Molecular Patterns. (1st February 2021) - Han, Yong Seop; Rivera-Grana, Erick; Rosenbaum, James T.; Schleisman, Matthew; Davin, Sean; Martin, Tammy M.; Furst, Alec B.; Asquith, Mark
ABSTRACT: Purpose: The innate immune system is strongly implicated in the pathogenesis of uveitis. This study was designed to clarify the responses of the innate immune system in uveal tissues. Materials and Methods: We utilized quantitative, real-time RT-PCR to measure mRNA of innate immune system receptors from porcine iris, choroid, and retina tissues. We used RT-PCR for cytokines to evaluate the responses of these tissues to specific ligands or extracts of whole bacteria that activate the innate immune system. We used ELISA for IL-6 on selected choroidal supernatants to confirm that the mRNA measurement correlated with protein levels. Results: In each of the studied tissues, we detected the expression of important receptors belonging to the innate immune system including dectin-1, TLR4, TLR8, and NOD2. Relative mRNA expression was generally lower in the retina compared to iris or choroid. All three tissues demonstrated upregulation of cytokine mRNA in response to a range of ligands that activate the innate immune system. The measurement of IL-6 protein was consistent with results based on mRNA. Notably, the expression of mRNA for IL-23 was more pronounced than IL-12 in all three tissues after stimulation with various innate immune system ligands. Conclusions: These data provide evidence of a potent innate immune response intrinsic to uveal tissues. Specific innate immune system ligands as well as bacterial extracts enhanced the production of several inflammatory cytokines. Furthermore, the observation of higher upregulation of IL-23 mRNA, compared to IL-12 in response to innate immune stimuli, suggested that a local TH17 response might be more robust than a local TH1 response in uveal tissues. Our results expand the understanding as to how the innate immune system may contribute to uveitis.